THE URGENCY OF TRANSITIONING FROM SOLITARY TO SOCIAL LEARNING TO CULTIVATE SOCIAL-EMOTIONAL COMPETENCIES IN PRE-SERVICE TEACHERS: A SYSTEMATIC LITERATURE REVIEW - Asri Widia Ningrum; Rohmani (International Journal of Multidisciplinary Reseach, 2026)
The transformation of education in the Society 5.0 era demands a paradigm shift in the teacher’s role, evolving from a mere transmitter of cognitive content to a skilled facilitator with mature Social-Emotional Competencies (SEC). Although Game-Based Learning (GBL) has been widely acknowledged as effective for developing general pedagogical competencies, this study identifies a critical gap in SEC training for pre-service teachers. Through a Systematic Literature Review (SLR) guided by PRISMA protocols, 32 articles were selected from five academic databases, enabling a thorough analysis of the limitations inherent in the solitary learning paradigm and the transformative potential of collaborative multiplayer approaches. Synthesis findings reveal that solitary learning simulations, which predominantly rely on interactions with Non-Player Characters (NPCs), significantly hinder the formation of SEC due to deterministic NPC responses, off-context dialogues, and a failure to elicit dynamic empathy and emotional regulation. In contrast, the collaborative multiplayer approach offers innovative solutions by facilitating authentic peer-to-peer interactions, dynamic scaffolding, and multimodal communication tools that enhance emotion recognition and regulation. These findings provide theoretical and architectural justification for the development of next-generation pre-service teacher simulation platforms that prioritize social learning for CASEL-grounded SEC development